Determinants of Financial Performance with Earnings Management as a Mediating Variable in Conventional Commercial Banks - Ahsanul Hadi Amin; Endah Susilowati; Dwi Suhartini (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the effect of good corporate governance, intellectual capital, accounting conservatism, and capital structure on financial performance with earnings management as a mediating variable. In this study, good corporate governance is proxied by the number of audit committees, boards of directors, and boards of commissioners. The intellectual capital variable is proxied by the value-added intellectual coefficient. In addition, accounting conservatism and capital structure variables are proxied by conservatism based on accrued items and debt-to-equity ratio, respectively. For earnings management and financial performance variables, each is measured by the value of discretionary accruals and return on assets. This research was conducted using quantitative methods with the object of research of conventional commercial banks. The population in this study was conventional commercial banks listed on the IDX, as many as 61 companies. The number of samples used in this study was 30 conventional commercial bank companies from 2019 to 2023, with a total of 150 data. This study uses secondary data in the form of annual reports from conventional commercial banks for the 2019-2023 period. Data analysis in this study was carried out using the Partial Least Squares (PLS) method with the help of the SmartPLS 4 application. The results showed that good corporate governance and intellectual capital have a positive influence on financial performance, while accounting conservatism and capital structure did not show a significant effect. This study also reveals that earnings management as a mediating variable does not successfully mediate the influence between good corporate governance, intellectual capital, accounting conservatism, and capital structure on the company's financial performance.